A case report on intraportal injection of autologous bone marrow-derived mononuclear cells and liver transplantation in a patient with cirrhosis - A. R. Sheraliev; A. A. Polikarpov; I. I. Tileubergenov; A. V. Moiseenko; D. A. Granov (Вестник трансплантологии и искусственных органов, 2021)
To date, liver transplantation remains the only effective treatment for patients with cirrhosis. Due to lack of other effective, alternative therapeutic methods, the search and development of new treatment technologies is problem number one. The development of cellular technologies is promising for use in clinical practice. Using this observation as an example, the safety and efficacy of cell therapy technology for prolonged stay on the liver transplant waiting list by a patient with cirrhosis is shown. After intraportal injection of autologous bone marrow-derived mononuclear cells, liver cirrhosis stabilized on the CTP and MELD-Na scales for 22 months of observation, which allowed the patient to wait for an organ and successfully undergo liver transplantation.